(untitled) (ItalianoLinguadue, 2025)
This paper examines the pitfalls of word-for-word translation in learning Italian as a second language (L2). Drawing on translation studies and language pedagogy, it highlights how literal translations often distort meaning by ignoring cultural, semantic, and pragmatic complexities. Contrary to the belief that direct translation ensures accuracy, this approach frequently leads to awkward or misleading results, e.g., rendering “over easy eggs” as uova super facilmente instead of uova fritte. Italian-specific structures and conventions, such as the formal Lei or idioms like in bocca al lupo, illustrate the deep cultural embedding of language. Three key factors contribute to word-for-word mistranslation: structural differences between Italian and English, false cognates that create semantic confusion, and cultural-pragmatic gaps in idioms and social norms. High-stakes fields like marketing, literature, and international relations underscore the risks of misinterpretation. Advocating a communicative, functional approach, this paper emphasizes the need for cultural literacy, awareness of traditions, idioms, and symbols. It outlines classroom strategies such as contrastive analysis, peer review, and selective technology use. Through examples and case studies, it argues that translation is a process of cultural mediation rather than mechanical substitution. Educators, learners, and professionals must go beyond one-to-one lexical correspondence to foster true intercultural communication. Lost in Translation: Le insidie del trasferimento linguistico parola per parola Questo articolo analizza le insidie della traduzione parola per parola nell’apprendimento dell’italiano come lingua seconda (L2). Basandosi su studi di traduzione e pedagogia linguistica, evidenzia come le traduzioni letterali spesso distorcano il significato, ignorando complessità culturali, semantiche e pragmatiche. Contrariamente alla convinzione che la traduzione diretta garantisca accuratezza, questo approccio porta frequentemente a risultati imprecisi o innaturali, ad esempio, tradurre over easy eggs come uova super facilmente invece di uova fritte. Strutture e convenzioni italiane, come il Lei formale o espressioni idiomatiche come in bocca al lupo, dimostrano il forte radicamento culturale della lingua. Tre fattori principali contribuiscono agli errori di traduzione letterale: le differenze strutturali tra italiano e inglese, i falsi amici che generano confusione semantica e le discrepanze culturali e pragmatiche negli idiomi e nelle norme sociali. Settori di alto profilo come il marketing, la letteratura e le relazioni internazionali mettono in luce i rischi di un’interpretazione errata. Sostenendo un approccio comunicativo e funzionale, questo studio sottolinea l’importanza della competenza culturale, la consapevolezza di tradizioni, espressioni idiomatiche e simboli culturali. Presenta strategie didattiche come l’analisi contrastiva, la revisione tra pari e l’uso selettivo della tecnologia. Attraverso esempi e casi di studio, dimostra che la traduzione è un atto di mediazione culturale, non una semplice sostituzione meccanica. Docenti, studenti e professionisti devono superare la corrispondenza lessicale uno-a-uno per promuovere una comunicazione interculturale autentica.